KONSELING PASTORAL DEFENSE MECHANISM PADA REMAJA PELAKU BULLYING - Brek, Yohan; Gloria Gresia Lomboan (POIMEN Jurnal Pastoral Konseling, 2024)
This study discusses the defense mechanisms of adolescent bullies, the factors that cause adolescents to use bullying as a form of defense mechanism and how defense mechanisms can be utilized as a pastoral counseling strategy. This study used the descriptive qualitative method. The data were obtained from observations, interviews and literature studies related to defense mechanisms for bullying adolescents. Where the defense mechanisms in adolescent bullies are irrational, destructive and aggressive. This is caused by an ego that has not yet developed and matured, as well as the bullies relationship with family, parents, peers, school and church. Therefore, through pastoral counseling, the bullies as the counselee will be assisted and directed to use a healthy defense mechanism. Defense mechanisms such as repression, diversion, reaction formation, regression and sublimation will be used as a pastoral counseling strategy. So negative defense mechanisms can be trained and diverted by processing or dealing with anxiety and conflicts in healthier manners. Defense mechanism can also be used to help bullies to stop using bullying as a defense mechanism through its use as a pastoral counseling strategy.